Enhancing the open-circuit voltage of perovskite solar cells by embedding molecular dipoles within their hole-blocking layer - Butscher, Julian; Intorp, Sebastian; Kreß, Joshua; An, Qingzhi; Hofstetter, Yvonne J.; Hippchen, Nikolai; Paulus, Fabian; Bunz, Uwe H. F.; Tessler, Nir; Vaynzof, Yana (ACS applied materials & interfaces, 2020)
Engineering the energetics of perovskite photovoltaic devices through deliberate introduction of dipoles to control the built-in potential of the devices offers an opportunity to enhance their performance without the need to modify the active layer itself. In this work, we demonstrate how the incorporation of molecular dipoles into the bathocuproine (BCP) hole-blocking layer of inverted perovskite solar cells improves the device open-circuit voltage (VOC) and, consequently, their performance. We explore a series of four thiaazulenic derivatives that exhibit increasing dipole moments and demonstrate that these molecules can be introduced into the solution-processed BCP layer to effectively increase the built-in potential within the device without altering any of the other device layers. As a result, the VOC of the devices is enhanced by up to 130 mV, with larger dipoles resulting in higher VOC. To investigate the limitations of this approach, we employ numerical device simulations that demonstrate that the highest dipole derivatives used in this work eliminate all limitations on the VOC stemming from the built-in potential of the device.